AFRICA'S PROSPECTIVE URBAN TRANSITION. (13th February 2017) - Collier, Paul
Abstract: The headline demographics of sub-Saharan Africa appear to be reason for concern. Looking back, since Independence in the 1960s, the region has been the major exception to the global demographic trend of rising height: In some countries, average height has even been declining [eLife (2016)]. Looking forward, between now and 2050, the population is set to grow more rapidly than that of any other region. But the demographic transition that is typically of most concern to African governments is not about the size or stature of overall population, it is urbanization. Politicians fear the consequences of a restive urban youth: an Arab Spring repeated south of the Sahara. Many would like to slow the pace of urbanization.